2018
DOI: 10.1080/02670836.2017.1415791
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and reliability of Mo nanoparticle reinforced Sn–58Bi-based lead-free solder joints

Abstract: The effect of Mo nanoparticles on the microstructure, wettability and mechanical properties of Sn–58Bi– xMo ( x = 0–2.00) solder joints was investigated. The results showed that the optimal wettability of Sn–58Bi–0.25Mo solder was obtained and the microstructure was refined by adding small amounts of Mo. The intermetallic compounds (IMCs) thickness was increased from Sn–58Bi 2.17 µm to Sn–58Bi–2Mo 2.73 µm. The tensile strength of Sn–58Bi solder joint was improved by adding 0.25 wt-% Mo. The fracture mode of Sn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 44 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…Nucleation sites in the melt reduce the free energy barrier and promote the nucleation events during solidification (Ref 12 ). Additives acting as a potent nucleation site in Sn-Bi solder have been previously reported for the addition of graphite NPs (Ref 15 ), Mo NPs (Ref 4 ) and BaTiO 3 NPs (Ref 5 ). The effectiveness of an additive in enhancing the nucleation event depends on the contact angle established between the additive and the nucleating phase.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Nucleation sites in the melt reduce the free energy barrier and promote the nucleation events during solidification (Ref 12 ). Additives acting as a potent nucleation site in Sn-Bi solder have been previously reported for the addition of graphite NPs (Ref 15 ), Mo NPs (Ref 4 ) and BaTiO 3 NPs (Ref 5 ). The effectiveness of an additive in enhancing the nucleation event depends on the contact angle established between the additive and the nucleating phase.…”
Section: Resultsmentioning
confidence: 90%
“…Addition of NPs in Sn-Bi solder alloy is an efficient way to improve the reliability of the solder joints by reducing the IMC thickness as well as refining the brittle Bi phase (Ref 3 ). NPs also enhance wettability (Ref 5 ), electro-migration performance (Ref 6 ), corrosion resistance (Ref 7 ) and reduce the coarsening of Bi phase upon aging (Ref 4 ). Wu et al (Ref 8 ) reported the addition of 1 wt.% ZnO NPs, substantially reduced the Cu-Ni-Sn thickness at the interface and increased the shear strength of Sn-57.6Bi-0.4Ag solder joints on Ni metallized Cu pads.…”
Section: Introductionmentioning
confidence: 99%
“…(b) A capillary phenomenon in which molten solder is sucked in the gap between two base metals, which is the recommendable gap in this case, is less than 0.3 mm. (c) The diffusion, which is the interatomic transfer between the solder and the base metal surface, must occur quickly [64]. In Sn-Bi-Sb solder, if Sb is added lower than 2 wt%, then the wettability of Sn-48%Bi will be improved [43].…”
Section: Effect Of Alloying Elements On Wetting and Spreading Of Sn-bi Soldermentioning
confidence: 99%